2005 June - ECOWAS (ECOWAS, 2005)
ECONOMIC COMMUNITY OF WEST AFRICAN STATES FIFTY-FOURTH SESSION OF THE COUNCIL OF MINISTERS, ABUJA, 23 JUNE 2005
Council of Ministers 23 June 2005
Keywords: Council of Ministers 23 June 2005